Percepções evidenciadas pelo coordenador pedagógico sobre a formação continuada de professores para a integração das tecnologias ao currículo - Szabo, Kelly (2014)
The aim of this paper is to investigate the highlighted perceptions by the pedagogical coordinator related to his role as teacher trainer for the integration of Digital Technologies Information and Communication into curriculum. The bibliography about the theme was studied to understand how it could contribute to this paper. The increasing usage of technologies at schools is shown as the aim and importance of its integration to the schools curriculum. Besides, it was possible to confirm that the role played by the pedagogical coordinator as trainer, is also an increasing concern, as well as all its other functions. However, it is still possible to have advance and contribute to the studies related to this theme. The research was done with the collaboration of five pedagogical coordinators from municipal public schools, that also were part of Project Khan Academy in Schools, which was closely followed by the writer/researcher who worked as a trainer and followed these coordinators mentioned above. The research is qualitative and has as strategy the content analysis. Apart from the collected data through questionnaires, interviews, School Regulations, a bibliography research was also done aiming to reinforce the studies and researches already available. It is understood that teachers training must fulfilled through transformation, improvement and practices that will bring real changes to teaching and learning processes. Thus, pedagogical coordinators perceive their roles as major factor to the integration of Digital Technologies Information and Communication into curriculum, they also see they need to be with teachers, working as partners, changing experiences and thoughts about the practice and prioritizing at schools, the daily topics, as example, the pedagogical usage of technology as an irreversible factor. However, boundaries still exist and its overcoming requires a day by day working. Integration of Digital Technologies Information and Communication into curriculum is only started in the studied schools